The Quality of Frozen Friesian Holstein Semen after Long-Term Storage - N. A. Bahmid; N. W. K. Karja; R. I. Arifiantini (Tropical Animal Science Journal, 2023)
Semen cryopreservation is the long-term storage at very low temperatures in liquid nitrogen for future use. This study investigates the quality of frozen Friesian Holstein (FH) semen after long-term storage. Samples of FH semen stored for 25, 20, 15, 10, 5, and 1 years were collected from one of the national centers for artificial inseminations. Frozen semen was stored in containers with liquid nitrogen at -196 ᵒC in a room with a temperature of 20 ᵒC The variables used after thawing were sperm motility, viability, and abnormalities, as well as plasma membrane integrity (IPM) using computer-assisted sperm analysis (CASA), eosin-nigrosine staining, and hypoosmotic swelling (HOS) test, respectively. Data were analyzed by one-way ANOVA and expressed as mean ± SEM. The result showed no significant differences in sperm viability, abnormalities, and IPM. Furthermore, sperm motility was >40%, consistent with the Indonesian standard for frozen bovine semen. CASA analysis showed that all variables of the motility pattern have no significant difference, except linearity (LIN). The Lin of sperm was lower in frozen semen after one and five years than after 20 and 25 years of storage. The overall quality of semen after 25, 20, 15, 10, 5, and 1 years of storage met the standard and was suitable for artificial insemination.